An Adaptive Virtual Impedance Based Droop Control Scheme for Parallel Inverter Operation in Low Voltage Microgrid - Nguyen Tien Hai; Kyeong-Hwa Kim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper presents an adaptive virtual impedance based droop control scheme for parallel inverter operation in low voltage microgrid. Because it is essential to achieve power sharing between inverters in microgrid, various droop control schemes have been proposed. In practice, the line impedance between inverters and the point of common coupling (PCC) in microgrid are not always equal. This imbalance in line impedance often results in a reactive power mismatch among inverters. This problem has been solved by introducing a virtual impedance loop in the conventional droop control scheme. However, the reactive power sharing performance of this method is still deteriorated when the line impedances change during operation. To overcome such a problem, a new control scheme that is based on a virtual impedance loop and an impedance estimation scheme is proposed. To monitor the changes in line impedances, the impedance estimator is implemented by using the output voltages and currents of inverters as well as the voltages at the PCC. To compensate for the reactive power mismatch due to the line impedance changes, the estimated line impedance is fed to the virtual impedance loop in which it adjusts the virtual impedance value. Comparative simulation results with the conventional ones verify the effectiveness of the proposed adaptive virtual impedance based droop control scheme.